Desempenho operacional e custos do harvester no desbaste de pinus taeda - Burgin, Mario Rodolfo Boff (2016)
This research aimed to evaluate the operating performance of the harvester in cutting loblolly Pinus taeda subjected to thinning regime in two terrain slope, aiming to help the planning of operations, increasing productivity and reducing production costs. The study was carried out in a forestry company located in the southern state of Paraná, in 10 years old Pinus taeda submitted to the first mixed thinning (systematic and selective), covering the land slope classes from 0° to 12° and 12.1° to 24°.. Technical analysis was conducted from a study of time and movement by multimomento method by analyzing the operating cycle and its operational interruptions and non-operational partial activities, and determining the mechanical availability and technical, operational efficiency, productivity and energy efficiency. The cost analysis was performed by the determination of operating and production costs. It's been estimated by regression equations, the harvester's productivity in of function of the declivity and individual volume of trees by selecting the best statistical model for machine productivity prediction. The results showed that partial activity that's consumed the longest time of the cutting operating cycle was the processing of trees, averaging 35.2% in both land slopes. The Harvester's productivity decreased along the increasing slope, reaching an average of 21.64 m³ cc h-1 and 19.40 m³ cc h-1 in classes from 0° to 12° and 12.1 to 24, making a production cost of R$ 8.65/m³ and R$ 10.15/m³, respectively. The machine's productivity decreased along the steepness of the terrain increasing, as well as increased as the volume of individual trees. The variables steepness and individual volume per tree estimated the productivity, with a determination coefficient of 0.98 with 10.49% standard error of the regression, demonstrating the influence of these variables on the machine's productivity.